Magnetic resonance venography to assess thrombus resolution with edoxaban monotherapy versus parenteral anticoagulation/warfarin for symptomatic deep vein thrombosis: A multicenter feasibility study. (August 2016) - Piazza, Gregory; Mani, Venkatesh; Goldhaber, Samuel Z; Grosso, Michael A; Mercuri, Michele; Lanz, Hans J; Schussler, Steven; Hsu, Ching; Chinigo, Amy; Ritchie, Bruce; Nadar, Venkatesh; Cannon, Kevin; et al.
The feasibility of magnetic resonance venography (MRV) for measuring change in thrombus volume with a novel anticoagulation regimen versus standard anticoagulation in patients with symptomatic deep vein thrombosis (DVT) has not been assessed. Our aim was to study the feasibility of MRV to measure change in thrombus volume in patients with acute symptomatic objectively confirmed proximal DVT in an open-label multicenter trial (edoxaban Thrombus Reduction Imaging Study, eTRIS). We randomized patients in a 2:1 allocation ratio to edoxaban 90 mg/day for 10 days followed by 60 mg/day versus parenteral anticoagulation bridging to warfarin for 3 months. The primary efficacy outcome was a surrogate end point of the relative change in MRV-quantified thrombus volume from baseline to Day 14–21. A total of 85 eligible patients from 26 study sites were randomized to edoxaban monotherapy ( n =56) versus parenteral anticoagulation as a 'bridge' to warfarin ( n =29). The mean relative change in MRV-quantified thrombus volume from baseline to Day 14–21 was similar in patients treated with edoxaban and parenteral anticoagulation as a 'bridge' to warfarin (−50.1% vs −58.9%; 95% confidence interval of treatment difference, −12.7%, 30.2%). However, thrombus extension was observed in eight patients in the edoxaban monotherapy group and in none in the warfarin group. Rates of recurrent venous thromboembolism (3.6% vs 3.6%, p =0.45) and clinically relevant non-major bleeding (5.4% vs 7.1%, p =0.34) were also similar. No major bleeds occurred in either on-treatment group during the study period. In conclusion, MRV can assess change in thrombus volume in patients with acute DVT randomized to two different anticoagulant regimens. ClinicalTrials.gov Identifier: NCT01662908 Investigational New Drug (IND) Application: Edoxaban IND # 63266